The Diagnosis of Abnormal Assembly Quality Based on Fuzzy Relation Equations. (19th January 2014) - Li, Dong-Ying; Zhang, Gen-Bao; Li, Meng-Qi; Liu, Jian; Cheng, Yan-Song
Abstract : The relationship between quality abnormality and anomalous causes in the assembly process of CNC machine was described by fuzzy relation equations, because they were not one to one. The fuzzy relation equations were established according to the fuzzy relation matrix and membership degree of abnormality mode and were translated into optimal solution problems by fuzzy deconvolution method. The interval solution of the fuzzy relation equation was obtained by minimal mean square error of BP algorithm, realizing section locating of the contribution of anomalous causes to quality abnormality for a given problem, thereby gaining the optimal solution. Finally, the viability and effectiveness of this method were verified by the quality abnormity diagnosis in the assembly process of a NC rotary table.